Evaluating the Effects of the Teen Outreach Program on Positive Youth Development Constructs - Rita DeBate (New Prairie Press, 2018)
Introduction: The Teen Outreach Program (TOP) is a positive youth development (PYD) program that seeks to reduce the risk of adolescent pregnancy, school dropout, and course failure. As TOP has not been evaluated for its impact on PYD constructs, our purpose was to assess this potential. Methods: A pair-matched, cluster randomized controlled trial to evaluate TOP among youth in 26 high schools was conducted in 2013-2014. Youth (N=3740) were surveyed at baseline and immediately following program completion. A linear mixed effects model compared scores of the Lerner’s Five Cs measure of PYD between treatment and control youth and by race/ethnicity and gender subgroups. Results: After a multiple comparison adjustment, no statistically significant results were observed.Conclusions: Despite the lack of statistically significant findings, the current study can provide insight for future evaluations of TOP regarding adaptation and evaluation of core components, implementation, PYD impacts, and sexual and reproductive health outcomes.